Measuring the subjective perceptions of the social censure of corruption in post-1997 Hong Kong - Li, Li (Crime, law and social change, 2016)
This study applies the social censure perspective to construct and validate a measurement scale that can map comprehensively the subjective perceptions of the social censure of corruption among District Councilors in post-1997 Hong Kong. Social censure theory emphasizes that corruption cannot be defined merely as a crime or deviant behavior. Instead, corruption is a complex concept with power, ideology, and conflict dimensions. First, using in-depth interview data from 20 respondents from Hong Kong and Guangzhou, the study mapped the main themes in connection with the problem of corruption in post-1997 Hong Kong and the changing relationship between Hong Kong and mainland China. Second, the first draft questionnaire was constructed based on the main themes coded from the interview data. Then, a pre-test was executed to revise and improve the question items in accordance with the direct feedback from the respondents. Using a pilot test, the revised questionnaire was validated. Afterwards, 148 District Council members were surveyed. A factor analysis was conducted and four subscales of 16 items were extracted. This process enabled the study to achieve innovative significance. The findings of this study provide a useful perspective upon which to understand existing corruption and relevant social phenomena in Hong Kong.